Meningkatkan Kemampuan Komunikasi Interpersonal Siswa melalui Layanan Penguasaan Konten dengan Teknik Sosiodrama - Agustiyana, Tina; Awalya, Awalya (Universitas Negeri Semarang, 2016)
The purpose for this research was to get empirical data about increase interpersonal communication as mastery of content service with technique sociodramas. Population of this study was class X of the SMA N 2 Ungaran was classes of X1-X11 and the sampel of class X8 which consist of 34 students was selected using purposive sampling technique. Data collection techniques were using psychological scale and observation. The instrument has been tested for validity using product moment and reliability of the instrument with alpha formula. Data analysis techniques used that is analysis descriptive percentage and t-test. The result of this research showed there was increase of interpersonal communication after be given conduct as mastery of content service with technique sociodramas as big as 8,6%. Based result t-test score tcount = 10,927> ttable = 2,042 or meaning Ha is accepted and Ho is rejected. So, result of this research is interpersonal communication can be increased as mastery of content service with technique sociodramas. Therefore, It is hoped that the teacher as a guide can be more intensively applicate mastery of content service with technique sociodramas to the students as an alternative strategy to help students increase interpersonal communication